PENILAIAN TINGKAT KESUKSESAN PENERAPAN INTELLIGENT TRANSPORT SYSTEM BERBASIS WEB Studi Kasus pada Dinas Perhubungan Pemerintah Kota Surakarta - , LILIYANA KURNIAWATI AFIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Â Intelligent Transport System ( ITS ) is an integrated system that is used for traffic management control system in Surakarta the volume of vehicles is increasing every year. The purpose of this study was to evaluate and obtain empirical evidence that the successful implementation of ITS was developed by the Department of Transportation and Communications ( Dishukominfo ) in Surakarta using models DeLone and McLean ( D & M ) updated. D & M is a model of successful testing of information technology systems that are based on the processes and causal relationships of the variables contained in the model. The variables in this model is, system quality, information quality, service quality, system use, user satisfaction, and net benefits. The method used is the method of quantitative survey methods to society Surakarta ITS applications that have used a total of 120 respondents. This study uses data analysis Structural Equation Modeling ( SEM ) with AMOS 18 aid applications to process data. The results of this study are variable ITS quality, information quality, and service quality significantly positive effect on the use of ITS. Variable ITS user satisfaction is influenced by three variables in this study, namely the quality of ITS systems, information quality and service quality. These three variables are significant except ITS user variables showed no effect on user satisfaction ITS. Perceived net benefit variable is affected by two variables, namely the use of ITS and ITS user satisfaction.